(untitled) (Scientific journal of the Fergana State University, 2025)
The article explores the concept of the national hero in literature as a reflection of national identity. Using the example of the Uzbek novel "The Golden Head of the Avenger" by Kh. Tukhtabayev and the Russian novel "I Came to Give You Freedom" by V. Shukshin, the features of creating the image of the folk hero, symbolizing the ideals and aspirations of the nation, are considered. The paper analyzes the characteristic traits of the folk hero, his role in preserving cultural heritage and shaping national identity. Special attention is given to the influence of historical and social factors on the perception of the folk hero in Russian and Uzbek literary traditions. The article helps to understand more deeply how through artistic images of folk heroes, literature contributes to the affirmation and strengthening of national consciousness.